PENGARUH ATRIBUT PRODUK TERHADAP LOYALITAS KONSUMEN KERUDUNG PRODUK RABBANI PADA KOMUNITAS MAHASISWI MUSLIM DI UNESA KETINTANG - ROSALIA, MEGA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Rabbani veil product attributes is the elements that matter to consumers one of which is the Muslim student community in Unesa Ketintang. Attributes include Rabbani hood design, brand image and color veil Rabbani. Rabbani hood design is attractive and has a great variety of design encourages the Muslim student community to keep selecting and using the veil Rabbani. Rabbani veils brand image that has been known since the first and consumers remain confident in the quality of the veil Rabbani. In addition, variations of color choices veil Rabbani also supports the consumer in choosing a veil reason Rabbani, Rabbani veil because the color is not flashy and in accordance with the wishes of consumers. Veil design, brand image and color which causes the veil Rabbani able to compete with its competitors and create loyalty in the Muslim student community Unesa Ketintang. This type of research has been carried out using the method of descriptive research with quantitative approach and a sample of 91 respondents from the Muslim student community in Unesa Ketintang. The analysis used is multiple linear regression analysis to test the hypothesis that the F test and t test. Based on the results of data processing distribution of respondents can be seen that Rabbani veil design conditions are strong in the area, the condition of brand image Rabbani veils are strong in the area, and the condition of the product color veil Rabbani was strong in the area. F test results show the design of the product (X1) has a very strong influence and significant impact on customer loyalty, brand image (X2) has a considerable and significant influence on consumer loyalty, while the color of the product (X3) does not have a significant effect on customer loyalty. The coefficient of determination equal to 0.943 or 94.3 % contribution shows a very strong influence. Keywords : product attributes and consumer loyalty